2021
DOI: 10.3390/microorganisms9040839
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Propyl Disulfide from Neem (Azadirachta indica) in Vapor and Agar Diffusion Assays against Anthracnose Pathogens (Colletotrichum gloeosporioides and Colletotrichum acutatum) in Mango Fruit

Abstract: Microorganisms causing anthracnose diseases have a medium to a high level of resistance to the existing fungicides. This study aimed to investigate neem plant extract (propyl disulfide, PD) as an alternative to the current fungicides against mango’s anthracnose. Microorganisms were isolated from decayed mango and identified as Colletotrichum gloeosporioides and Colletotrichum acutatum. Next, a pathogenicity test was conducted and after fulfilling Koch’s postulates, fungi were reisolated from these symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
1
9
0
1
Order By: Relevance
“…The characteristics of the studied isolate causing anthracnose on mango in this study were consistent with the description of Sutton [ 13 ] regarding Colletotrichum spp. Furthermore, these characteristics were similar to those of Colletotrichum acutatum described in the studies of Khan et al [ 56 ], Jayasinghe et al [ 57 ], Sundelin et al [ 58 ], and Peres et al [ 59 ].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The characteristics of the studied isolate causing anthracnose on mango in this study were consistent with the description of Sutton [ 13 ] regarding Colletotrichum spp. Furthermore, these characteristics were similar to those of Colletotrichum acutatum described in the studies of Khan et al [ 56 ], Jayasinghe et al [ 57 ], Sundelin et al [ 58 ], and Peres et al [ 59 ].…”
Section: Resultssupporting
confidence: 85%
“…The mycelial growth was relatively slow—after 9 days of inoculation, the mycelial diameter in the Petri dish was about 5.5 cm. Mycelium of C. acutatum reached the edge of the Petri dish at about 14 days, while the mycelial growth rate of C. gloeosporioides was relatively fast and reached the edge of the Petri dish at about 10 days [ 56 ]. The upper colony surface was white, while the lower colony surface had a light orange color.…”
Section: Resultsmentioning
confidence: 99%
“…The plates were photographed with a Canon digital camera and analyzed by using the graphic software "Fiji ImageJ" (GNU General Public License). Finally, the PIG was calculated using the following formula [38].…”
Section: Plos Onementioning
confidence: 99%
“…However, in our previous study on mango fruit, we found that PD was very efficient in inhibiting the growth of major fungi in mango fruit samples. We found that PD effectively inhibited the mycelial growth of Colletotrichum gloeosporioides and Colletotrichum acutatum , causing anthracnose, as well as Lasiodiplodia theobromae and Neofusicoccum parvum, causing stem end rots in mango [ 14 , 15 ]. Future research should be directed toward the specific microorganisms found in longan fruit samples.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on controlling plant diseases. Propyl disulfide compound is the major volatile compound in neem plant seeds, and our research group previously assessed the antifungal activity levels of propyl disulfide, which effectively inhibited the mycelial growth of fungi, which causes anthracnose [ 14 ] and stem end rot [ 15 ] in mango fruit, obtaining very promising results. Zakawa et al [ 16 ] studied the effects of neem leaf extract on the fungi causing anthracnose in wild mango.…”
Section: Introductionmentioning
confidence: 99%